Influence of Rainfall Fluctuations on Population Trends of Eleven Wild Herbivores in Soysambu Conservancy, Kenya - Kimanzi, Johnstone K.; Mbau , Caroline W. (African Journal of Education,Science and Technology (AJEST), 2019)
Recent studies have shown that about 70% of wildlife populations are found outside the protected areas in Kenya. In a bid to cater for this large portion of wildlife many conservancies have been established in Kenya. Soysambu is one of the private conservancies that has experienced consistent decline in rainfall during the dry seasons. This may cause decline in wildlife populations in this conservancy as their declines have been shown to be directly correlated with decreases in rainfall unlike in other private conservancies. This study was carried out to determine the population trends of eleven wild herbivores, the effect of temporal variation in rainfall on wild herbivore populations and establish the relationship between wild herbivore populations in Soysambu conservancy. Data for twentyone years (1993-2013) on rainfall and wild herbivore populations were obtained from the conservancy records and the Kenya meteorology service. Regression and correlation analyses were used to assess population trends, relationship between rainfall parameters (wet season, dry season, mean annual, and 5-year cumulative rainfalls) and herbivore populations, and correlation among herbivore populations. Results showed a significant increase in the population of impala (r2 = 0.267, P = 0.004), buffalo (r2 = 0.511, P < 0.001), zebra (r2 = 0.745, P < 0.001), giraffe (r2 = 0.786, P < 0.001), herbivore browsers (r2 = 0.5641, P < 0.001) and grazers (r2 = 0.748, P < 0.001), but a significant decrease in the population of Thomson’s gazelle (r2 = 0.387, P = 0.007). The significant increase in the populations of zebra, giraffe and all grazers were attributed to the increase in mean annual rainfall and decrease in dry season rainfall. Also, the significant decrease in the population of Thomson’s gazelle was attributed to the significant decrease in dry season rainfall (r2 = 0.321, P = 0.022) and the increase in the populations of zebra (r = -0.654, n = 21, p = 0.040) and giraffe (r = -0.654, n = 21, P = 0.001). The increase in the other herbivore populations could not be explained by rainfall variability. Pearson correlation showed that there was a significant positive correlation between browsers and grazers (r = 0.745, n = 21, P < 0.001) and significant correlations (P < 0.05) among 10 wild herbivore species. For sustainable conservation of diverse wild herbivores in Soysambu conservancy there is need to (i) provide artificial water supply to species that are water-dependent and significantly decreasing to counter the adverse effects of drought, (ii) regulate the populations that are significantly increasing at the expensive of others and (iii) carry out further research to understand habitat requirements of the various herbivore species and identify resource inadequacies before they threaten population viability.